2009
DOI: 10.1123/japa.17.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Frail Institutionalized Elderly: Effects of a Cognition-Action Intervention and Tai Chi

Abstract: No previous studies have explored the effects of mind–body approaches on health-related quality of life (HRQoL) in the frail elderly. Cognition and action are an inseparable whole during functioning. Thus, a new intervention-based approach using familiarity-based movements and a nonjudgmental approach of “cognition-action” was proposed and was tested with Tai Chi on HRQoL in frail institutionalized elderly. Fifty-two participants (58% women) age 65–94 took part in a 24-wk Tai Chi (TC) intervention 4 days/wk or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 36 publications
(27 reference statements)
3
79
1
3
Order By: Relevance
“…Three studies examined the effects of long-term Tai Chi Chuan practice on cognition using the Mini Mental State Examination (MMSE), and the findings of these studies were not consistent (Burgener, Yang, Gilbert, & Marsh-Yant, 2008;Deschamps et al, 2009;Nowalk et al, 2001).…”
Section: Tai Chi Chuan and Cognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies examined the effects of long-term Tai Chi Chuan practice on cognition using the Mini Mental State Examination (MMSE), and the findings of these studies were not consistent (Burgener, Yang, Gilbert, & Marsh-Yant, 2008;Deschamps et al, 2009;Nowalk et al, 2001).…”
Section: Tai Chi Chuan and Cognitionmentioning
confidence: 99%
“…However, there was no significant difference in MMSE performance from 20 to 40 weeks, which indicated that 20 weeks might be sufficient for cognitive gains as a result of this intervention. Deschamps et al (2009) compared the effects of an intervention called cognition-action (which consists of lower body muscle exercise, upper and core body exercises, and deep breathing and relaxation) with those of Tai Chi Chuan in 52 frail older adults age 65-94 years. The Tai Chi Chuan consisted of the Yang style for 24 weeks, four times a week, for 30 min per class.…”
Section: Tai Chi Chuan and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30] Table 2 includes 9 studies in populations that reported varying degrees of cognitive impairment, ranging from MCI to irreversible dementia. 9,[31][32][33][34][35][36][37][38][39] Eight studies were conducted in the United States, 7 in China, 3 in France, and 1 in both Japan and Vietnam. All but one study 22 focused on older adults with average ages above 60.…”
Section: Study Designsmentioning
confidence: 99%
“…El TCC ha sido relacionado con la capacidad de producir numerosos beneficios sobre la salud física y mental de sus practicantes: a nivel cardiorrespiratorio (Brown et al, 1989), sobre la osteoartritis (Brismeé et al, 2007;Ni et al, 2010;Song et al, 2003), el equilibrio (Fong & Ng, 2006;Gyllensten et al, 2010;Tsang et al, 2004;Wong et al, 2001), el miedo a las caídas (Taggart, 2002;Wolf et al, 1996;Zhang et al, 2006), la depresión, la ansiedad, el ánimo y el estrés (Brown et al, 1995;Galantino et al, 2005;Jin, 1989;Taylor et al, 2006;Toda et al, 2011), la autoestima (Blake y Batson, 2009), la auto-eficacia (Dechamps et al, 2009;Lee et al, 2009;Taylor y Froelicher, 2004), etc. A nivel psicológico, se ha catalogado incluso como "meditación en forma de movimiento" por la capacidad del TCC de sumir a sus practicantes en estados de gran tranquilidad y relajación mental (Taylor et al, 2006;Wang et al, 2010a).…”
Section: Introductionunclassified